Uma possível correlação entre a energia de Casimir e os hidretos supercondutores. - Junior, Eric Barcelos Rangel (2022)
Since its discovery in 1911, superconductivity has great scientific relevance due to its high potential of technological application in several areas, such as production and transmission of electricity, medicine, public transportation, etc. The discovery of materials that are superconducting at room temperature and of a microscopic theory that fully explains this phenomenon are one of the main challenges of modern science. In the last years, superconductivity at high temperatures has been observed in hydrogen rich materials submitted to high pressures, like the carbonaceous sulfur hydride, which presented the superconducting state at room temperature when submitted to a pressure of approximately 267 GPa. In this work a possible correlation between the Casimir Energy and the superconducting state of hydrides presenting superconductivity was developed. We apply the Casimir Energy model between two thin plasma sheets in order to estimate their effective mass and compare it with the results in the bibliography obtained for other non-conventional superconductors.